Integrating Counseling Management and Multicultural Education: A Model for Enhancing Students’ Learning Motivation - Erta Apriata; Okke Rosmaladewi, (Journal of Science and Education (JSE), 2025)
This study explores the management of guidance and counseling (GC) programs as a strategic instrument to enhance students’ learning motivation in multicultural junior high schools. Using a qualitative case study design, the research was conducted at SMPN 1 Ciawi and SMPN 3 Ciawi in Tasikmalaya Regency, Indonesia, involving school principals, guidance and counseling teachers, and students. Data were collected through in-depth interviews, participant observations, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The results indicate that effective GC management implemented through systematic planning, participatory execution, reflective evaluation, and continuous follow-up contributes significantly to improving students’ academic motivation and emotional engagement. The planning phase involves data-based analysis and goal setting; implementation combines individual mentoring and peer-based support within a culturally responsive framework; evaluation emphasizes collaborative reflection and authentic feedback; and follow-up actions include mentoring continuity, teacher collaboration, and parent involvement. These findings highlight that counseling management, when guided by the PDCA (Plan–Do–Check–Act) model and integrated with multicultural and humanistic counseling principles, serves as a sustainable approach to strengthening student motivation and holistic character formation.